Analysis Of Depression in Stroke Patients Using BDI-II (Beck Depression Index-II) - Endrian MJW; Ayuni Zahra; Ade Fitriani (Asy-Syifa : Journal of Science and Technology Nursing, 2026)
Purpose: The purpose of this study was to describe the level of depression among stroke patients using the Beck Depression Inventory-II (BDI-II) instrument. Methods: This study employed a prospective cohort design conducted over approximately three months. The sample consisted of 40 stroke patients treated in the Mawar ward of Ciamis Hospital. Participants were selected using a purposive sampling technique. Data were collected using the BDI-II questionnaire to assess depression levels. The study was conducted from March to May 2023. Results: The findings showed that out of 40 ischemic stroke patients, 12 patients experienced depression. Among them, 8 patients (20%) had mild depression, 3 patients (7.5%) had moderate depression, and 1 patient (2.5%) had severe depression. The most frequently reported symptoms were related to anxiety and sadness. Conclusions: Depression is present among stroke patients with varying levels of severity and may be influenced by multiple factors. Psychological symptoms such as anxiety and sadness are commonly experienced. Therefore, early screening and appropriate psychological support are important in the management of stroke patients.